2020
DOI: 10.14720/aas.2020.116.1.1563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV-C radiation on basic indices of growth process of winter wheat (Triticum aestivum L.) seeds in pre-sowing treatment

Abstract: <p>An investigation of the effects of UV-C radiation from source having the power of 20 W on improvement of seed quality of Ukrainian winter wheat (<em>Triticum aestivum </em>L.) six cultivars: ‘Gratsіia Myronivska’, ‘Trudivnytsia Myronivska’, ‘Vezha Myronivska’, ‘Mudrist Odeska’, ‘Nyva Odeska’ and ‘Lira Odeska’, has been done. In the performed experiment the UV-C irradiation in the range of 50-1000 J m<sup>-2</sup> was applied. Based on the experimental results it is concluded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Передпосівну обробку насіння для вирощування за традиційної технології здійснювали ультрафіолетовим (УФ) опромінюванням лампою типу ZW20D15W потужністю 20 Вт дозою 150 Дж/м 2 згідно з методикою, описаною в роботі [11]. Указана доза була встановлена експериментально через опромінення 6 сортів пшениці озимої (Triticum aestivum L.) УФ-С-променями діапазону 50-1000 Дж/м 2 .…”
Section: матеріали і методиunclassified
“…Передпосівну обробку насіння для вирощування за традиційної технології здійснювали ультрафіолетовим (УФ) опромінюванням лампою типу ZW20D15W потужністю 20 Вт дозою 150 Дж/м 2 згідно з методикою, описаною в роботі [11]. Указана доза була встановлена експериментально через опромінення 6 сортів пшениці озимої (Triticum aestivum L.) УФ-С-променями діапазону 50-1000 Дж/м 2 .…”
Section: матеріали і методиunclassified
“…Відстань від ламп до сітки з насінням становила 25 см. Брали до уваги досвід використання УФ-С опромінення для стимулювання насіння моркви [16], пшениці озимої [17], оптимальною була визнана доза 200 Дж/м 2 .…”
Section: матеріали і методи дослідженьunclassified
“…[5][6][7][8]. According to Semenov et al [9], UV-C irradiation stimulated seed vigor and germination in the seed quality of winter wheat cultivars. The study found UV-C irradiation, at specific optimal doses per cultivar, enhanced seed quality in terms of vigor, germination rate, and seedling development in the 6 Ukrainian wheat cultivars tested.…”
Section: Introductionmentioning
confidence: 99%